SULTAN TERNATE ISKANDAR DJABIR SYAH DAN PETUALANGANNYA DALAM NEGARA INDONESIA TIMUR, 1946-1950 - Rustam Hasyim; Faisal Faisal; Rasti Amalia Faruk (Universitas Khairun, 2018)
This study aims to reconstruct the political participation of Iskandar Djabir Syah (the 47thSultan of Ternate) in the establishment of the State of Eastern Indonesia. The study focuses on outlining some political events involving Iskandar Djabir Syah such as the Malino and Denpasar conferences and becaming the Minister of Home Affairs of the Eastern Indonesia State for 1949 to 1950 periods. The method used in this paper is a heuristic method that is history, criticism, interpretation and historiography. The results showed that: (1) the participation of Sultan of Ternate Iskandar Djabir Syah in the unitary state started in the early independence of the Republic of Indonesia; it was characterized by conducting Malino and Denpasar conferences in 1946. The establishment of the Eastern Indonesia State became the political inspiration for Iskandar Djabir Syah to involve as the senate member of the Eastern Indonesia State/NIT representing North Maluku, as well as one of its designers. (2) As one of the leaders who agreed to the idea of van Mook to form a federalist country in the Malino and Denpasar conference, so that when the Eastern Indonesia State was formed, he was appointed as the Minister of Home Affairs in the cabinet of J.E. Tatengkeng for 1949 to 1950 periods. (3) Malino to Denpasar Conference in 1946 initiated by H.J. van Mook was the Dutch effort to establish the states in order to realize the United States of Indonesia (Republik Indonesia Serikat/RIS) based on Linggarjati Agreement. At the conference, it was formed the Eastern Indonesia State (Negara Indonesia Timur/NIT) covering the areas of Sulawesi, Small Sunda (Bali and Nusa Tenggara) and the Maluku Islands.Keywords: Sultan of Ternate Iskandar Djabir Syah, Political History, Malino and Denpasar Conferences, the Minister of Home Affairs of Eastern Indonesia State (NIT)